Optimalisasi Penggunaan Software Pengolah Kata Bagi Siswa Madrasah Aliyah Al-Washliyah Medan - Ali Akbar Lubis; Muhammad Dedi Irawan (Jurnal IPTEK Bagi Masyarakat, 2021)
Microsoft Office Word is one of the most widely used word processing applications in Indonesia. At Madrasah Aliyah Al-Washliyah, students have learned how to use Microsoft Office Word, but are limited to the basic features. In this community service, students and students of Madrasah Aliyah Al-Washliyah are trained to use the References feature in creating a table of contents and bibliography automatically. The purpose of this community service is to improve the ability of students in optimizing the use of Microsoft Office Word, especially in making a table of contents and bibliography.